3(2n+5)=8(7n+8)+6

Simple and best practice solution for 3(2n+5)=8(7n+8)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2n+5)=8(7n+8)+6 equation:


Simplifying
3(2n + 5) = 8(7n + 8) + 6

Reorder the terms:
3(5 + 2n) = 8(7n + 8) + 6
(5 * 3 + 2n * 3) = 8(7n + 8) + 6
(15 + 6n) = 8(7n + 8) + 6

Reorder the terms:
15 + 6n = 8(8 + 7n) + 6
15 + 6n = (8 * 8 + 7n * 8) + 6
15 + 6n = (64 + 56n) + 6

Reorder the terms:
15 + 6n = 64 + 6 + 56n

Combine like terms: 64 + 6 = 70
15 + 6n = 70 + 56n

Solving
15 + 6n = 70 + 56n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-56n' to each side of the equation.
15 + 6n + -56n = 70 + 56n + -56n

Combine like terms: 6n + -56n = -50n
15 + -50n = 70 + 56n + -56n

Combine like terms: 56n + -56n = 0
15 + -50n = 70 + 0
15 + -50n = 70

Add '-15' to each side of the equation.
15 + -15 + -50n = 70 + -15

Combine like terms: 15 + -15 = 0
0 + -50n = 70 + -15
-50n = 70 + -15

Combine like terms: 70 + -15 = 55
-50n = 55

Divide each side by '-50'.
n = -1.1

Simplifying
n = -1.1

See similar equations:

| 7x-3x+45=180 | | (4b-5)(-3b+2)= | | 2(5)+-5y=10 | | M-17=-25 | | 1.7c=-39.1 | | (2x)+54.2=180 | | 3and1/2=28 | | x(9-3x)= | | 5n-6=7n | | -14+5s+10q-3s-3q+4= | | 2x+4(-3+-14)=34 | | 48=2z+4z | | 0=6+rx+4x | | 1=-10w+9w | | 0=6+4x+rx | | 21x^2+20x+4=0 | | x/5=52/65 | | 0=4x+rx+6 | | X+114+x+40+106+100=360 | | -8=192 | | m^2+20m+c=0 | | X+5y=22.5 | | 10u-21=34 | | 81-1=8x | | fuck=bitch+1 | | -2(5x-7)=-16 | | 3/7xk=6 | | 3.9+b=14.4 | | d+.05=.75 | | 30x+5y=35 | | x-5=-4x+16 | | x+55=67 |

Equations solver categories